Different modes of spacer acquisition by the Staphylococcus epidermidis type III-A CRISPR-Cas system. Issue 3 (20th January 2022) - Aviram, Naama; Thornal, Ashley N; Zeevi, David; Marraffini, Luciano A
Abstract: CRISPR-Cas systems provide prokaryotic organisms with an adaptive defense mechanism that acquires immunological memories of infections. This is accomplished by integration of short fragments from the genome of invaders such as phages and plasmids, called 'spacers', into the CRISPR locus of the host. Depending on their genetic composition, CRISPR-Cas systems can be classified into six types, I-VI, however spacer acquisition has been extensively studied only in type I and II systems. Here, we used an inducible spacer acquisition assay to study this process in the type III-A CRISPR-Cas system of Staphylococcus epidermidis, in the absence of phage selection. Similarly to type I and II spacer acquisition, this type III system uses Cas1 and Cas2 to preferentially integrate spacers from the chromosomal terminus and free dsDNA ends produced after DNA breaks, in a manner that is enhanced by the AddAB DNA repair complex. Surprisingly, a different mode of spacer acquisition from rRNA and tRNA loci, which spans only the transcribed sequences of these genes and is not enhanced by AddAB, was also detected. Therefore, our findings reveal both common mechanistic principles that may be conserved in all CRISPR-Cas systems, as well as unique and intriguing features of type III spacer acquisition.